“Analisis of learning difficulties in the speaking skill aimed at segundo de bachillerato “e“at “Unidad Educativa Riobamba” located in Riobamba, Chimborazo Province, during academic period february-june 2016. - Coro Roldan, Willian Israel (2016)
This research project is based in the analysis of learning difficulties in the speaking skill that students have in the moment to express in oral communication particularly it develop at Unidad Educativa Riobamba, Chimborazo province, Riobamba city during academic period February June 2016.The main objective of this investigation is to explore the learning difficulties in the speaking skill in the students of Segundo de Bachillerato “E” Because the development of this skill is consider one of the most harder during the learning process of a second language. In fact, the confusion of ideas, words or the low production affected the student’s presentation. In the academic period it applied a guide observation with different factor and items where the students make the same errors. As a result, it was suggested some recommendations and conclusions. The interpretation of the result was made through the collection of evidence with different photographs. The exploratory method was used in this research project. And finally it used the ethnographic which helped to describe analyze, explore, clarify the ideas of the problem mentioned.